INTERNATIONAL REGULATIONS IN CAPITAL STANDARDS IN INSURANCE COMPANIES AND BANKING SYSTEM OF SERBIA - Milić, Dragana T.; Milošević, Snežana; Ercegovac, Dajana (International Journal of Economic Practice and Policy, 2015)
The emergence and expansion of the recent financial crisis has renewed the question of regulation and supervision of the financial system. Therefore, the question of managing financial risks is becoming increasingly popular and gaining more and more importance. Regulators have in recent years introduced capital standards based on specific sensitivity to risk. Based on defined issues, the starting point is the general hypothesis that the capital adequacy is a key base for measuring the resistance of the banking and insurance sector to market shocks. This paper will present the analytical, synthetic and general scientific methods. The comparative method is used in this paper to highlight the similarities and differences between Solvency II and Basel III and their operational efficiency.
Keywords: Solvency II; Bazel III; capital adequacy; risk management